Detection of a Diffuse Extended Halo-like Structure around 47 Tuc - Piatti, Andres Eduardo (2017)
We constructed for the first time a stellar density profile of 47 Tucanae (47 Tuc) out of ∼5.5 times its tidal radius (r t) using high-quality deep BV photometry. After carefully considering the influence of photometric errors, and Milky Way and Small Magellanic Cloud composite stellar population contamination, we found that the cluster stellar density profile reaches a nearly constant value from ∼1.7r t outward, which does not depend on the direction from the cluster's center considered. These results visibly contrast with recent distinct theoretical predictions on the existence of tidal tails or on a density profile that falls as at large distances, and with observational outcomes of a clumpy structure as well. Our results suggest that the envelope of 47 Tuc is a halo-like, nearly constant low-density structure.